The 1926/27 Soviet polar census expeditions - Anderson, David G. (David George), 1965- (Berghahn Books, Inc., 2011)
"This a much-welcome addition to the modern English-language reference library on Siberian Indigenous people and the first book-size effort to address their plight and status from the perspective of the Russian archival statistical and documentary records of the early 1900s. It is an outcome of a monumental collaborative project." * Igor Krupnik, Smithsonian Institution. In 1926/27 the Soviet Central Statistical Administration initiated several yearlong expeditions to gather primary data on the whereabouts, economy and living conditions of all rural peoples living in the Arctic.